2021
DOI: 10.3390/s21134464
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Sensor System for Sea Water Iodide Monitoring and Seafood Quality Assurance: Proof-of-Concept Study

Abstract: Iodine is a trace chemical element fundamental for a healthy human organism. Iodine deficiency affects about 2 billion people worldwide causing from mild to severe neurological impairment, especially in children. Nevertheless, an adequate nutritional intake is considered the best approach to prevent such disorders. Iodine is present in seawater and seafood, and its common forms in the diet are iodide and iodate; most iodide in seawater is caused by the biological reduction of the thermodynamically stable iodat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…To implement remedial procedures or keep track of public health, it is necessary to monitor the changing concentration of contaminants over time. Scientists have methods to assess and monitor seawater quality [15][16][17][18], but another method using biosensors has gained a lot of attention in recent years due to its effectiveness as an analytical instrument and its superior capabilities for monitoring pollution and public health. This testing is quick, easily implemented, inexpensive, onsite, and only needs a small instrument to monitor multiple pollutants at once.…”
Section: Introduction 1seawater Quality Challengesmentioning
confidence: 99%
“…To implement remedial procedures or keep track of public health, it is necessary to monitor the changing concentration of contaminants over time. Scientists have methods to assess and monitor seawater quality [15][16][17][18], but another method using biosensors has gained a lot of attention in recent years due to its effectiveness as an analytical instrument and its superior capabilities for monitoring pollution and public health. This testing is quick, easily implemented, inexpensive, onsite, and only needs a small instrument to monitor multiple pollutants at once.…”
Section: Introduction 1seawater Quality Challengesmentioning
confidence: 99%
“…It has been concluded that the most accurate quality indicators were provided by the artificial neural network machine-learning model and satellite data. Similarly, Zompanti et al [14] concentrated on monitoring the sea water iodide for assuring the quality of seafood. A multi-sensor approach was proposed to evaluate the seawater iodate level and thus to assess the quality of seafood.…”
Section: Specific Water-quality Monitoring Applicationsmentioning
confidence: 99%